Pengaruh Work Life Balance, Motivasi Kerja, Dan Kepuasan Kerja Terhadap Loyalitas Karyawan Di Rumah Sakit Yasyfin Darussalam Gontor Ponorogo - Sindi Wahyuningrum; Sri Hartono; Dwi Warni Wahyuningsih (Departement of Mathematics Education, 2024)
This research aims to determine the influence of work life balance, work motivation, job satisfaction on employee loyalty at Yasyfin Darussalam Gontor Ponorogo Hospital. This research uses a non-probability sampling method, namely using the entire population of 63 employees. The data collection technique in this research was by distributing questionnaires to employees of Yasyfin Darussalam Gontor Ponorogo Hospital. The data in this research was processed using the SPSS application. The results obtained were that partially work life balance had a positive and significant effect on employee loyalty. These results mean that the work life balance variable has an influence on employee loyalty at Yasyfin Darussalam Gontor Ponorogo Hospital. Work motivation has a positive and significant effect on employee loyalty. These results mean that the work motivation variable has an influence on employee loyalty at Yasyfin Darussalam Gontor Ponorogo Hospital. Job satisfaction has a positive and significant effect on employee loyalty. These results can be interpreted that the job satisfaction variable has an influence on employee loyalty at Yasyfin Darussalam Gontor Hospital Ponorogo. Work life balance, work motivation and job satisfaction together have a positive and significant effect on employee loyalty. This means that the variables Work life balance, work motivation and job satisfaction simultaneously influence employee loyalty at Yasyfin Darussalam Gontor Ponorogo Hospital.